Sustainable Exports to the European Union from ASEAN Countries: Is There an Impact of Low Carbon Economy? - Nikensari, Sri Indah; Nurdiyanto, Ega; Sing Yun, Wong; Zahra, Siti Fatimah (International Journal of Energy Economics and Policy, 2024)
Trade and climate change are thought to be closely related. Sustainable trade cooperation with European Union (EU) countries is often linked to the issue of climate action and low carbon emissions. This research aims to examine the low carbon economy and the economic distance of ASEAN countries (Indonesia, Malaysia, Philippines, Singapore, Thailand) towards their exports to EU countries. A low carbon economy is measured by the intensity of GHG emissions, analysed from three scopes, namely CO2 from manufacturing and industrial processes (part of scope-1), CO2 from electricity consumption (part of scope-2), and CO2 from waste (part of scope- 3). Data source from Emissions Database for Global Atmospheric Research (EDGAR) and other sources, 2012-2022. Panel data regression with a gravity model is used in this analysis. The results show the implementation of a low carbon economy in ASEAN, so that in the future there seems to be continued trade between ASEAN countries and the EU. This is proven by the negative influence of carbon emission intensity scope-2, scope-3, and economic distance on increasing ASEAN exports, except scope-1. Low intensity means there is efficient use of resources for the economy, and low economic distance means trade is competitive.